Desmoplakin is required for epidermal integrity and morphogenesis in the Xenopus laevis embryo. - Bharathan, Navaneetha Krishnan (Dev Biol, 2019)
Desmoplakin (Dsp) is a unique and critical desmosomal protein, that is integral to epidermal development. However, it is unclear whether this protein is required specifically for epidermal morphogenesis. Using morpholinos or Crispr/Cas9 mutagenesis we decreased the function of Dsp in frog embryos to better understand its role during epidermal development. Dsp morphant and mutant embryos had developmental defects such as epidermal fragility that mimicked what has been reported in mammals. Most importantly, we also uncovered a novel function for Dsp in the morphogenesis of the epidermis in X. laevis. In particular, Dsp is required during the process of radial intercalation where basally located cells move into the outer epidermal layer. Once inserted these newly intercalated cells expand their apical surface and then they differentiate into specific epidermal cell types. Decreased levels of Dsp resulted in the failure of the radially intercalating cells to expand their apical surface, thereby reducing the number of differentiated multiciliated and secretory cells. Such defects correlate with changes in E-cadherin levels and actin and microtubule localization which could explain the defects in apical expansion. A mutated form of Dsp that maintains cell-cell adhesion but eliminates the connections to the cytoskeleton results in the same epidermal morphogenesis defect. These results suggest a specific role for Dsp in the apical expansion of cells during radial intercalation. We have developed a novel system, in the frog, to demonstrate for the first time that desmosomes not only protect against mechanical stress but are also critical for epidermal morphogenesis.